2011
DOI: 10.1097/sla.0b013e31822518be
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of Contrast-Enhanced Intraoperative Ultrasound Using Sonazoid in Patients With Hepatocellular Carcinoma

Abstract: With help of CE-IOUS using Sonazoid, more accurate intraoperative staging for HCC can be performed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 48 publications
(61 reference statements)
2
52
0
Order By: Relevance
“…The most used second-generation contrast medium is SonoVue (gaseous sulphur hexafluoride; Bracco, Milano Italy), which nowadays has a recognized diagnostic role for liver disease [22]. Recently, in Japan a new second-generation contrast medium has been used, Sonazoid (gaseous perflubutane; GE Healthcare, Norway), that has the advantage of Kupffer imaging in addition to vascular imaging, thus theoretically providing greater diagnostic accuracy [23]. …”
Section: Staging Of Hccmentioning
confidence: 99%
“…The most used second-generation contrast medium is SonoVue (gaseous sulphur hexafluoride; Bracco, Milano Italy), which nowadays has a recognized diagnostic role for liver disease [22]. Recently, in Japan a new second-generation contrast medium has been used, Sonazoid (gaseous perflubutane; GE Healthcare, Norway), that has the advantage of Kupffer imaging in addition to vascular imaging, thus theoretically providing greater diagnostic accuracy [23]. …”
Section: Staging Of Hccmentioning
confidence: 99%
“…The conventional intraoperative ultrasonography and the enhanced ultrasonography using some contrast medium are also helpful for us to understand the anatomic relationship between the important vessels (such as IRHV) to be preserved and tumor border intraoperatively [19,20]. The significance of the IRHV preserving liver resection is now increased by the remarkable advance in the surgery-related techniques and devices.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this ability, CE-IOUS using Sonazoid enables the detection of new HCC tumors that are unidentifiable either by preoperative imaging modality or by IOUS [11]. Recently, the authors reported CE-IOUS to be useful in clearly visualizing the border of tumors during laparoscopic hepatectomy for which energy devices are frequently used [33].…”
Section: Contrast-enhanced Iousmentioning
confidence: 99%
“…Diagnostic accuracy of CE-IOUS to differentiate HCC among nodules that are intraoperatively identified by IOUS is reported to be approximately 80% [10,11] (table 1). In addition to this ability, CE-IOUS using Sonazoid enables the detection of new HCC tumors that are unidentifiable either by preoperative imaging modality or by IOUS [11].…”
Section: Contrast-enhanced Iousmentioning
confidence: 99%
See 1 more Smart Citation